2007
DOI: 10.3122/jabfm.2007.03.060127
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Evaluation and Intervention During Family Medicine Well Visits

Abstract: Purpose: The purpose of this study was to determine the extent that primary care providers assess overweight and obesity and offer treatment strategies during well visits in a family medicine setting.Methods: This was a cross-sectional study of 553 consecutive patients who presented for family medicine well visits. Patient charts were reviewed for documentation of body mass index (BMI) and patient education regarding weight, exercise, and diet.Results: BMI was calculated for 63.5% of adults at the well visit. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
17
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 17 publications
3
17
0
Order By: Relevance
“…In a 2007 study of 140 primary care physicians (PCPs) by Bardia et al,only 19.9% of obese patients had a recorded diagnosis of obesity and 22.6% had a documented obesity management plan [10]. Boardley et al ascertained that the 47 family medicine physicians they studied had calculated a BMI for 63.5% of patients with a BMI >25 kg/m 2 and half or less of these patients had received education on weight loss through diet and exercise [11]. Ma et al performed an analysis of the 2005 and 2006 National Ambulatory Medical Care Survey (NAMCS).…”
Section: Introductionmentioning
confidence: 98%
“…In a 2007 study of 140 primary care physicians (PCPs) by Bardia et al,only 19.9% of obese patients had a recorded diagnosis of obesity and 22.6% had a documented obesity management plan [10]. Boardley et al ascertained that the 47 family medicine physicians they studied had calculated a BMI for 63.5% of patients with a BMI >25 kg/m 2 and half or less of these patients had received education on weight loss through diet and exercise [11]. Ma et al performed an analysis of the 2005 and 2006 National Ambulatory Medical Care Survey (NAMCS).…”
Section: Introductionmentioning
confidence: 98%
“…In one primary care setting, BMI was calculated for only 64% of adults during the first visit. 46 For patients who were overweight or obese, only 49% received education on weight loss, 50% on diet, and 41% on exercise.…”
Section: Reviewmentioning
confidence: 99%
“…16,17 Another recent study found that pediatricians identified training, time, and resources as barriers to BMI use. 18 Among family physicians, use of an electronic health record (EHR) significantly increased the use of BMI and increased documentation and treatment of obese (but not overweight) adults.…”
mentioning
confidence: 99%
“…Height and weight were calculated for 95% of the children, but none had BMI calculated; the authors recommended that family physicians use BMI for age for children and adolescents. 16 Clinicians rarely document overweight, although they perceive high BMI more seriously than weight and height measures.…”
mentioning
confidence: 99%